Perbandingan Hukum Cryptocurrency Sebagai Alat Tukar Menurut Fatwa MUI dengan Perspektif Ustadz Adi Hidayat - efendi, Rahmad Satria Efendi; Ahda Bina; Anggraeni, Luciana (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2023)
The purpose of this research is to enhance knowledge about the rights related to cryptocurrency law for readers and to provide an understanding of Ustadz Adi Hidayat's views on the MUI fatwa regarding the use of cryptocurrency. This research is used to analyze the comparison between the Indonesian Ulema Council (MUI) fatwa and Ustadz Adi Hidayat's perspective. The research is conducted using a library research method, which involves using literature as a data source. The data collected come from various library materials, scholarly works, books, YouTube, online media, and others related to the discussion of using bitcoin in transactions. The approach used is a normative approach, studying the position of bitcoin as electronic currency.The results of this research are as follows: First, from Ustadz Adi Hidayat's perspective, cryptocurrency is considered haram (prohibited) because it contains elements of harm (dharar) and uncertainty (gharar). Second, the Indonesian Ulema Council (MUI) fatwa states that cryptocurrency is haram due to the presence of harm (dharar), uncertainty (gharar), and gambling (qimar). However, it is deemed legally valid as a medium of exchange if the asset meets the conditions of being a lawful commodity (sil'ah) and has clear underlying assets and benefits.